Методи подолання стресу - Петрик, Галина (Видавництво Національного університету "Львівська політехніка", 2009)
Stress is basic part of vital functions of everybody, that is why each must know as possible to be delivered stress, especially during a crisis. Select three phases stress which have a different influence on a man. It is known that stress influences on a man not only negatively, but also on occasion even positively, it is therefore needed to be able by them to manage, understanding itself and the reactions even in difficult situations.
Keywords: stress; stress-managemen; phases of stress